Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian Konsumen Indihome PT. Creative Widya Nusantara - Yuli Krisma Wati; Rokh Eddy Prabowo (IPM2KPE, 2023)
This research aims to analyze the influence of product quality and price perception on consumer purchasing decisions of IndiHome PT. Creative Widya Nusantara. The method used is a quantitative research method. The population in this research are all consumers of IndiHome PT. Creative Widya Nusantara. The total sample was 97 respondents determined using purposive sampling technique. The data analyzed is primary data collected using a questionnaire and processed using SPSS version 24. The research results, the results of the coefficient of determination (R2) test, show that the ability of the independent variable to explain the dependent variable is 54.7 percent. The t test results show that all independent variables are declared significant. The results of the regression coefficients for all independent variables are declared positive. Conclusion, that the independent variables, namely product quality and price perception, partially or simultaneously have a positive and significant effect on consumer purchasing decisions of IndiHome PT. Creative Widya Nusantara. Keywords: IndiHome, Purchase Decision, Product Quality, Price Perception